Observations Regarding Expanded Verbal Adverbials with the Meaning of Intention Accompanied by the Postposition İçi̇n (for, in Order To) - Edina Solak; Mirza Bašić; Asja Mešić (Društvene i Humanističke Studije)
This paper analyzes grammatical and semantic features of expanded verbal adverbials with the meaning of intention, which are formed through postpositional constructions where the postposition için (for, in order to) functions as the postpositional component. The analysis is divided into three parts and it is based on descriptive analytics as well as contrastive approach. The primary source consists of examples from Kemal Tahir’s novels titled Esir Şehrin İnsanları, Esir Şehrin Mahpusu and Yol Ayrımı. The first part of the paper analyzes grammatical and semantic features of single-subject sentences, where the subject of the expanded verbal adverbial with the meaning of intention accompanied by the postposition için (for, in order to) is identical to the subject of the correlative predicate to which the adverbial group with the meaning of intention is subordinated. The second part of the paper deals with the analysis of multi-subject sentences in which the subject of the expanded verbal adverbial accompanied by the postposition için (for, in order to) is not identical to the subject of the correlative predicate to which the adverbial group with the meaning of intention is subordinated. The third part analyzes examples where expanded verbal adverbials with the meaning of intention accompanied by the postposition için (for, in order to) are subordinated to an infinitive correlative predicate. Within the framework of contrastive analysis, expanded verbal adverbials with the meaning of intention accompanied by the postposition için (for, in order to) are compared with semantically similar syntactic constructions in Bosnian language. Such analysis contributes to a better and easier understanding of expanded verbal adverbials with the meaning of intention, which are expressed through postpositional constructions where the postposition için (for, in order to) functions as a postpositional component.